Tindakan Hukum Terhadap Terduga Teroris Dalam Perspektif Hukum Islam, Hukum Positif, dan Hak Asasi Manusia - Amin, Khoironi Faisal, Muchamad Iksan, S.H., M.H (2017)
The purpose of this research is to know the legal action done by the law enforcement officer towards the suspect of terorism in Islamic law perspective, Indonesian's positive law, and Human Rights. This research employs a research method that is descriptive normative law approach. The kind of this research is descriptive normative research. Data used is from the secondary sources which is consist of primary law sources, secondary law sources and tertiary law sources. The data collection technique used in this research is though literature study. The result of this research in Islamic law perspective is based on Quran and Hadist. The next is the legal action towards the suspect of terorism in positive law perspective is based on the KUHAP and the Terorism Constitution, and the last is the legal action towards terorism suspects in Human Rights perspective is based on Human Rights Constitution. The conclusion of this research is there still can be found the violation on field done by the law enforcement officer in handling the suspect of terorism where contradictive with 3 (three) rules of law that are Islamic law, Indonesian Positive law and Human Rights.